Collaboration and guidelines for the coordination of health care for frail older persons with intellectual disability: A national survey of nurses working in municipal care. Issue 3 (29th December 2020) - Ahlström, Gerd; Hansson, Jan‐Åke; Kristensson, Jimmie; Runesson, Ingrid; Persson, Magnus; Bökberg, Christina
Abstract: Aims: To describe and compare perceptions of collaboration between care providers on the part of three groups of Registered Nurses working in municipal care and having particular responsibility concerning the care of frail older people with intellectual disability (ID); and, furthermore, to investigate the presence of and compliance with guidelines for the coordination of care. Design: National survey study with cross‐sectional design. Methods: Nurses ( N = 110) with key positions concerning people with ID answered a national questionnaire about collaboration, guidelines and coordinated individual plans. Descriptive and comparative statistical analyses were applied. Results: The meetings on cooperation and coordination of interventions were attended most frequently by nurses, and least frequently by social workers. The nurses were overall satisfied with the collaboration but perceived shortcomings in the case of inpatient and outpatient psychiatric care. Only in about half of the meetings for making care plans participated the people with intellectual disability and next of kin.